Teacher Burnout and Well-being: A Bibliometric Review of 25 Years of Research - Abdul Wafi; Benny Prasetiya; Febry Suprapto; Khoiriyah Khoiriyah (Green Publisher, 2026)
Teacher burnout is a growing global issue, particularly in the context of prolonged stress and its impact on educators' physical and emotional health, as well as their professional efficacy and overall well-being. This phenomenon has garnered increasing attention over recent years, especially since the COVID-19 pandemic, which exacerbated stressors faced by teachers, leading to higher burnout rates. This study aims to provide a bibliometric review of research on teacher burnout and well-being over the past 25 years, mapping out key trends, influential authors, and the major topics explored in this field. Using systematic literature review (SLR) guidelines and data from the Scopus and Web of Science databases, the study examines publication patterns, collaboration networks, and prevalent research themes. The results highlight a significant rise in publications related to teacher burnout post-pandemic, with a particular emphasis on emotional exhaustion, work engagement, and well-being interventions such as mindfulness and physical activities. Additionally, the review identifies gaps in the literature, such as a lack of focus on the long-term consequences of burnout and the systemic factors that contribute to it. The contribution of this study is twofold: it expands the understanding of teacher burnout by synthesizing a large body of literature and provides insights for future research, particularly in terms of effective interventions and addressing systemic issues within educational institutions.